Alternative method for canagliflozin oxidation analysis using an electrochemical flow cell - Comparative study - Vymyslický, Filip; Křížek, Tomáš; Kozlík, Petr; Kubíčková, Anna; Heřt, Jakub; Bartosińska, Ewa (Journal of pharmaceutical and biomedical analysis, 2022)
This paper highlights the potential of electrochemical flow cells for oxidative-stress testing of active pharmaceutical ingredients using canagliflozin as a model substance. Based on design of experiments, we developed our method through a reduced combinatorial design, optimizing the following independent variables: cell size, electrolyte flow rate, electrolyte concentration, and electrolyte pH. Using ammonium phosphate buffer with methanol in a 50/50 vol ratio as a working electrolyte, we electrochemically oxidized samples and analyzed them by high-performance liquid chromatography, considering the following dependent variables: peak area of each impurity, peak area of canagliflozin, and the percentage of the corresponding peak areas. Our results showed that the most significant independent variables were electrolyte pH and flow rate. By data optimization, we determined the most suitable conditions for electrochemical oxidation of canagliflozin, namely 50 µm cell size, 300 mM electrolyte concentration, 0.1 mL/h electrolyte flow rate, and electrolyte pH = 4. The repeatability of the method, expressed as the relative standard deviation of the canagliflozin peak area, measured in ten separately oxidized samples, was 1.64%. For comparison purposes, we performed a degradation experiment using hydrogen peroxide, identifying five identical impurities in both cases, as confirmed by mass spectrometry. The degradation products formed when using the chemical method after 1, 3, and 7 days totaled 0.09%, 0.75%, and 3.75%, respectively, and the degradation products formed when using the electrochemical method after 3 h totaled 3.11%. Oxidation with hydrogen peroxide required 7 days, whereas electrochemical oxidation was completed in 3 h. Overall, the electrochemical method significantly saves time and reduces the consumption of active ingredients and solvents thanks to the miniaturized size of the electrochemical cell, thereby minimizing the costs of forced degradation studies.
Keywords: elektrochemické techniky; hmotnostní spektrometrie; Canagliflozin; Electrochemical Techniques; Mass Spectrometry; vysokoúčinná kapalinová chromatografie; oxidace-redukce; canagliflozin; Chromatography, High Pressure Liquid; Electrochemical oxidation; Electrochemical flow cell; Stress testing; Oxidation-Reduction; Degradation; Design of experiments